Foreign language anxiety and self-perceived English pronunciation competence - Szyszka, Magdalena (Studies in Second Language Learning and Teaching, 2011)
In foreign language learning a negative correlation has been reported be-tween language anxiety and both oral performance (Liu, 2006; Stephenson Wilson, 2006; Woodrow 2006) and self-perceived levels of speaking ability (Kitano, 2001; MacIntyre, Noels, & Clement, 1997; Piechurska-Kuciel, 2008). However, little is known about the relationship between language anxiety and the way students perceive their own competence regarding one of the integral components of oral performance – pronunciation. The present study is an attempt to investigate the link between foreign language anxiety and the self-perceived levels of pronunciation of 48 teacher training college students, who study English as a foreign language. A negative correlation, r = -.54 (p < .05), was found between the level of their language anxiety and self-perceived English pronunciation competence, indicating that more apprehensive teacher trainees perceived their pronunciation as poor, whereas those with lower levels of anxiety declared higher pronunciation competence. Moreover, statistically significant negative correlations were noted between the levels of anxiety and self-perceived competences of several suprasegmental aspects of pronunciation, such as word pronunciation, stress, weak forms, rhythm, linking, and assimilation. The teacher trainees who rated their competence of these suprasegmentals more highly experienced lower levels of foreign language anxiety. The perception of segmentals, however, appeared to be unconnected with the participants’ anxiety.